What’s Antecedent Driving Intention To Purchase Organic Food? Examining Attitude and Trust - Riptiono, Sulis; Wiwoho, Gunarso; Rhamdhani, Intan Muliana (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Organic food has its own appeal for consumers, so the development of the organic food business is currently rapid. Choosing the right food is the main key in maintaining health by living a healthy lifestyle. Purpose: Thus, this research aims to examine antecedents that can increase consumer purchase intentions for organic food in Central Java.Design/Methodology/approach: A total of 242 of organic food consumers as the respondent were involved to fill out the survey with a questionnaire determined based on purposive sampling techniques. The collected data was processed and analysed using structural equation models with the help of AMOS statistical tools.Finding/Result: The research results prove that consumer purchase intentions for organic food are influenced by consumer attitudes and beliefs in organic food, but are not influenced by food safety concerns. Meanwhile, consumer trust in organic food is influenced by food safety concerns and health consciousness is not significant. Furthermore, attitude toward organic food is influenced by food safety concerns and health consciousness.Conclusion: This research concludes that the antecedents used in this research have an important role in increasing consumer purchase intentions towards organic food.Originality/value (state of the art): The originality of this research is that this research contributes to providing different insights regarding antecedents that can increase consumer purchasing intentions for organic food. Keywords: green marketing, purchase intention, organic food, health consciousness, food safety